2017
DOI: 10.1126/scitranslmed.aam7049
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic action of the MCL-1 inhibitor S63845 with current therapies in preclinical models of triple-negative and HER2-amplified breast cancer

Abstract: The development of BH3 mimetics, which antagonize prosurvival proteins of the BCL-2 family, represents a potential breakthrough in cancer therapy. Targeting the prosurvival member MCL-1 has been an area of intense interest because it is frequently deregulated in cancer. In breast cancer, MCL-1 is often amplified, and high expression predicts poor patient outcome. We tested the MCL-1 inhibitor S63845 in breast cancer cell lines and patient-derived xenografts with high expression of MCL-1. S63845 displayed syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 67 publications
7
127
1
Order By: Relevance
“…These observations (GSEA findings) led us to hypothesize that LXR agonists synergize with BH3 mimetics (ABT263). Therefore, we conducted cellular viability assays with dose–responses of each drug, followed by drug combination treatment and synergy analysis based on the Chou–Talalay method, which enables the calculation of normalized isobolograms (median‐effect equation) (Chou, ; Karpel‐Massler et al , 2017c; Merino et al , ). Selected conditions of the single and combination treatments are provided and statistically compared (Fig G–N and Appendix Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…These observations (GSEA findings) led us to hypothesize that LXR agonists synergize with BH3 mimetics (ABT263). Therefore, we conducted cellular viability assays with dose–responses of each drug, followed by drug combination treatment and synergy analysis based on the Chou–Talalay method, which enables the calculation of normalized isobolograms (median‐effect equation) (Chou, ; Karpel‐Massler et al , 2017c; Merino et al , ). Selected conditions of the single and combination treatments are provided and statistically compared (Fig G–N and Appendix Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, $85% of ER-positive breast cancers express high levels of BCL-2 (Dawson et al, 2010) and, accordingly, venetoclax and navitoclax synergized with tamoxifen in inhibiting the growth of patient-derived xenografts in mice (Vaillant et al, 2013). MCL-1 inhibitors, such as S63845, were also shown to efficiently inhibit the growth of triple-negative as well as HER-2-positive breast cancers when combined with chemotherapy or HER2-targeted therapies (Kotschy et al, 2016;Leverson et al, 2015b;Merino et al, 2017;Xiao et al, 2015;Young et al, 2016). Neuroblastoma growth was attenuated by inhibition of either BCL-2 or MCL-1 (Bate-Eya et al, 2016;Tanos et al, 2016), and the combination of venetoclax with the aurora kinase A inhibitor MLN8237 achieved complete remission in a patientderived xenograft of MYCN-amplified neuroblastomas (Ham et al, 2016).…”
Section: Impact Of Combinations Of Bh3-mimetics With Standard-of-carementioning
confidence: 99%
“…The BCL-2 inhibitor Venetoclax is highly efficacious for the treatment of relapsed/refractory Chronic Lymphocytic Leukemia (CLL) Stilgenbauer et al, 2016). A clinically relevant specific and potent inhibitor of MCL-1, called S63845 (Kotschy et al, 2016), has been shown to be efficacious as a single agent in several pre-clinical models of haematological malignancies and in combination with oncogenic kinase inhibitors in certain lung, skin as well as breast cancer derived cell lines and patientderived xenograft models (Kotschy et al, 2016;Merino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%